A review on major business excellence frameworks. - Dodangeh, J.; Rosnah, M.Y.; Ismail, N.; Md.Ismail, Y.; Biekzadeh, M.R.; Jassbi, J. (Social Science Research Network, 2013)
Link to publisher's homepage at http://papers.ssrn.com